Marrow Adipose Tissue: Its Origin, Function, and Regulation in Bone Remodeling and Regeneration - Qiwen Li; Yunshu Wu; Ning Kang (Stem Cells International)
Marrow adipose tissue (MAT) is a unique fat depot in the bone marrow and exhibits close relationship with hematopoiesis and bone homeostasis. MAT is distinct from peripheral adipose tissue in respect of its heterogeneous origin, site-specific distribution, and complex and perplexing function. Though MAT is indicated to function in hematopoiesis, skeletal remodeling, and energy metabolism, its explicit characterization still requires further research. In this review, we highlight recent advancement made in MAT regarding the origin and distribution of MAT, the local interaction with bone homeostasis and hematopoietic niche, the systemic endocrine regulation of metabolism, and MAT-based strategies to enhance bone formation.